Gandhi’s Political Philosophy - Parekh, B.C. author. aut Link
IX, 248 p.
Keywords: An attempt to provide a critical account of Gandhi's moral and political philosophy. It places him in an historical context and examines his central philosophical assumptions, drawing on his original Gujarati works and discussions with his associates and followers.